Peran Kepala Sekolah Dan Guru Dalam Menumbuhkan Perilaku Hidup Sehat Pada Siswa SD Bakti II Medan - Suyono Suyono; Anggun Dela Puspita; Annisa Balqis; Naila Audiva Hutasuhut (Departement of Mathematics Education, 2024)
The purpose of this research is to find out and describe the role of school principals and teachers in fostering healthy living behaviors in students at the Bakti II Medan State Elementary School. The method used in this research is descriptive qualitative by using data collection techniques through interviews, observation and documentation. Then the data analysis techniques used are data reduction, data presentation and conclusions. The results of this study are the daily behavior of elementary school-aged children who show concern for their own health and theenvironment, in the following behaviors : breakfast before going to school, eating regularly, snacking in a clean canteen/stall, eating healthy food, washing hands thoroughly. Clean soap and water before eating, brushing teeth, cleaning nails and hair, maintaining cleanliness of school toilets, using clean clothes, using clean shoes and socks, disposing of garbage in its place, cleaning classrooms and school environment, getting used to clean living in home, as well as participating in sports and physical activitieson a regular basis. This research is intended so that the role of principals and teachers can motivate students to maintain a healthy school environment, in order to independently avoid disease.